Air Defense Efficiency Analysis of “Detecting, Guiding, Interfering and Damaging” Multi-Functional Directed Energy Weapons - Wu Taotao, He Miao, Xia Liangbin, Wang Qian, A Jingye (Hangkong bingqi)
As directed energy weapons are neither well-integrated nor maximizing their effectiveness in the modern defense system, this paper proposes the multi-functional application of directed energy weapons for“detecting, guiding, interfering and damaging”, that is to use the ultra-high intensity electromagnetic radiations emitted by directed energy weapons, establishing signal-level cooperation with the radar, seeker and other sensors in the equipment system, to achieve detection, guidance, interference, damage and other operational effectiveness, improving the efficiency of the overall air defense. Then, basic principles and development status of multi-functional directed energy weapons are analyzed through literature investigation. After the air defense operational scenario of typical point is constructed, this research carries out combat simulations with the multi-agent modeling method of simulation software, comparing and analyzing the anti-UAV swarms combat effectiveness of three different equipment systems, namely “air defense missiles”“air defense missiles + single-functional directed energy weapons” and “air defense missiles + multi-functional directed energy weapons”. The simulation results show that the multi-functional application of directed energy weapons can effectively improve the anti-saturation attack capability and anti-high-speed swarms capability of the air defense system.